Les fonds de cabane du haut Moyen Âge en Île-de-France, réexamen du corpus et de la typologie à l’aune de la fouille de Bonneuil-en-France (95) “Aéroport du Bourget, zone nord-ouest” - Cyrille Ben Kaddour (Revue Archéologique du Centre de la France)
The preventive archaeological excavation at Bonneuil-en-France carried out in 2010/2011 and 2016/2017 enabled to study most of a large settlement (more than10 ha) from the late 5th or early of 6th century to the 11th century. It compounded numerous Sunken Featured Buildings (FSB). Their study has incited to examine the last 30 years discoveries, to update the former syntheses of F. Gentili et M. Deschamp (2009) and question the typo-chronological and functionnal aspects of these structures in the rural settlements of Île-de-France.